2012
DOI: 10.3748/wjg.v18.i13.1479
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents indomethacin-induced gastropathy in rats

Abstract: The results indicate that curcumin prevents indomethacin-induced gastropathy through the improvement of gastric microcirculation by attenuating the level of ICAM-1 and TNF-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…For example, it was reported that curcumin may be useful for treating gastric injuries by gastric peroxide inhibition, ROS, leukocyte infiltration inhibition, and reduction of the cell adhesion molecule level (ICAM-1) and tumor necrosis factor alpha (TNF-a) (23) . Another study about NSAID-induced gastric damage showed that curcumin can increase catalase and superoxide as well as nitric oxide levels in the gastric mucosa (6,25) . The beneficial effects of curcumin on gastritis can be created by the inhibition of gastric acid production due to inhibition of histamine receptors (14) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that curcumin may be useful for treating gastric injuries by gastric peroxide inhibition, ROS, leukocyte infiltration inhibition, and reduction of the cell adhesion molecule level (ICAM-1) and tumor necrosis factor alpha (TNF-a) (23) . Another study about NSAID-induced gastric damage showed that curcumin can increase catalase and superoxide as well as nitric oxide levels in the gastric mucosa (6,25) . The beneficial effects of curcumin on gastritis can be created by the inhibition of gastric acid production due to inhibition of histamine receptors (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can also prevent indomethacin-induced gastropathy by improvement the gastric microcirculation through attenuating the level of intercellular adhesion molecule (ICAM)-1and TNFα levels compared to treatment with indomethacin alone [57]. IL-1 genetic polymorphisms influenced H. pylori-related gastric mucosal IL-1β levels which may lead to gastric inflammation and atrophy; factors thought to be important in gastric carcinogenesis [58], it can be speculated that curcumin potentially plays a role in this aspect.…”
Section: Abbas Et Almentioning
confidence: 99%
“…The method was carried out as described by [32]. The following concentrations of VVE and vitamin C (standard antioxidant) concentrations were prepared 10,20,30,40,50,60,70, and 80 mg/ml in each tube. 2 ml of DPPH; (250 mm DPPH/200 ml methanol) then added the certain concentration of each extract, and adjust the final volume to be 4 ml with methanol.…”
Section: Determination Of Antioxidant Activity (Free Radical Scavengimentioning
confidence: 99%
“…Indomethacin was administered as the single oral dose (150 mg/kg) [40] dissolved in 5% sodium bicarbonate [41], and the rats were kept in cold stress for 2 h at a temperature of 3-5 ° C [42].…”
Section: Induction Of Severe Gastric Ulcers (Sgu)mentioning
confidence: 99%